POSITIVISME HUKUM DALAM PROSEDUR LEGISLASI DI INDONESIA - Arikatul Firdaus; Mahir Amin; Sri Warjiyati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Legal positivism and legislative procedures in Indonesia Focus on formal legality which often causes the resulting laws to reflect less social justice or the moral values ​​of society. Based on Lack of Public Participation, legislative procedures include public consultation; in practice, public participation is often considered a mere formality. Law as a Political Product: The dominance of competent authorities in legislation often makes law a political instrument rather than a tool for realizing justice. The basis of Positivism in Legislation in Indonesia is that legal Positivism is reflected in the Indonesian legal system through the Hierarchy of Legislative Regulations.